The relationship between career growth and organizational commitment among employees in Lembaga Hasil Dalam Negeri (LHDN) Sarawak/ Muhammad Safwan Saifullah Othman - Othman, Muhammad Safwan Saifullah (2018)
The title of this study is the relationship between career growth and organizational commitment among employees. The purpose of this study is to investigate the relationship between the four aspects of career growth (Career Goal Progress, Professional Ability Development, Promotion Speed, and remuneration Growth) and organizational commitment. This study was done at Lembaga Hasil Dalam Negeri (LHDN) Sarawak, located in Kuching, Sarawak. The outcome of this study is there is a significant positive relationship between career growth and organizational commitment. There are positive, moderate and significant relationship between career goal progress and organizational commitment (r=.488**) (p>0.01), professional ability development and organizational commitment (r=.594**) (p>0.01), promotion speed and organizational commitment (r=.393**) (p>0.01), and remuneration growth and organizational commitment (r=.533**) (p>0.01). The positive correlation coefficient indicates that an increase in career growth led to increase in organizational commitment.